Brand Value Destinations: Tourist Experience Can Improve Revisit Intention - Setiawan, Rahyuniati; Saepuloh, Asep; Herlianti, Anggun Oktavia (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
Competition in tourism destinations makes companies have to be able to attract new tourists and also retain existing customers by continuously innovating. The research objective of analyzing tourist experience on revisit intention and its impact on destination brand value is to obtain findings regarding the effect of tourist experience on revisit intention and its impact on destination brand value. This research was conducted on the largest hot spring tourist attraction in Garut Regency. The research method used is the verification research method, using PLS-SEM analysis and in quantitative research data analysis is carried out after the data of all respondents have been collected. The results of this study indicate that the influence of tourist experience on revisit intention and an impact on the brand value of the destination.